2009
DOI: 10.1137/080725842
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a One-Dimensional Nonlocal Quasi-Continuum Method

Abstract: Abstract. The accuracy of the quasicontinuum method is analyzed using a series of models with increasing complexity. It is demonstrated that the existence of the ghost force may lead to large errors. It is also shown that the ghost force removal strategy proposed by E, Lu and Yang leads to a version of the quasicontinuum method with uniform accuracy.Key words. Quasicontinuum method, ghost force, geometrically consistent scheme AMS subject classifications. 65N12, 65N06, 74G20, 74G151. Introduction. The quasicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 31 publications
1
98
0
1
Order By: Relevance
“…Our error estimate in Theorem 5.1 shows that the ℓ 2 strain error for the BQCE method can be reduced by a factor of k 3/2 where k is the number of atoms in the blending region. This result is suggested by the results of [13,29] on the decay of the coupling error for QCE. It has been shown that the QCE method suffers from a O(1) error in the critical strain at which the lattice loses stability (which models fracture or the formation of a defect) [16].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our error estimate in Theorem 5.1 shows that the ℓ 2 strain error for the BQCE method can be reduced by a factor of k 3/2 where k is the number of atoms in the blending region. This result is suggested by the results of [13,29] on the decay of the coupling error for QCE. It has been shown that the QCE method suffers from a O(1) error in the critical strain at which the lattice loses stability (which models fracture or the formation of a defect) [16].…”
Section: Introductionmentioning
confidence: 52%
“…Our analysis includes the optimization of the blending function for an improved convergence rate. We show that the ℓ 2 strain error for the non-blended QCE energy (QCE), which has low order O(ε 1/2 ) where ε is the atomistic length scale [13,29], can be reduced by a factor of k 3/2 for an optimized blending function where k is the number of atoms in the blending region. The QCE energy has been further shown to suffer from a O(1) error in the critical strain at which the lattice loses stability [16].…”
mentioning
confidence: 99%
“…Energy-based methods in this class, such as the quasicontinuum model (denoted QCE [38]), exhibit spurious interfacial forces ("ghost forces") even under uniform strain [8,36]. The effect of the ghost force on the error in computing the deformation and the lattice stability by the QCE approximation has been analyzed in [8,9,11,26]. The development of more accurate energy-based a/c methods is an ongoing process [5,16,20,31,35,37].…”
mentioning
confidence: 99%
“…The error of the QCL method is of course dominated by the "defect". It is also very interesting to note that, in this particular problem, the error in the QCE method due to the ghost force [5,23,31] is even larger than the error committed by the QCL method due to describing the "defect" with the continuum model. Repeating the test with κ = 3, which is shown in Figure 5, gives rise to an interesting observation.…”
Section: Test 1: a Deep Equilibriummentioning
confidence: 99%
“…By contrast, force-based coupling mechanisms [4,16,15,31] are comparatively simple in their formulation and, more importantly, they do not suffer from the interfacial consistency errors exhibited by most energybased methods [5,23]. The force-based quasicontinuum (QCF) method [4] is a prototypical example of a force-based atomistic/continuum hybrid method and is the focus of the present paper.…”
Section: Introductionmentioning
confidence: 99%